Telaah Tugas dan Tanggung Jawab Guru di Era Society 5.0 - Yusfita Sari; Jihan Salma Pusaka; Farouq Al-Ashil; Rully Hidayatullah; Hadeli Hadeli (Lembaga Pengembangan Kinerja Dosen, 2025)
Social transformation brought by the Industrial Revolution 4.0 has led to the emergence of Society 5.0, where technology is integrated into all aspects of life. In education, this presents both challenges and opportunities, especially for teachers whose roles and responsibilities have become increasingly complex. This article aims to analyze the strategic role of teachers in shaping student competencies relevant to the demands of the 21st century. Using a descriptive qualitative approach and library research method, the study refers to constructivism, connectivism, and the 21st Century Skills Framework. The findings highlight that teachers must balance mastering educational technology with instilling character values in students. Their responsibilities include fostering critical thinking, communication, collaboration, creativity (4C), promoting digital literacy, and preparing students as global citizens. The study concludes that teachers are key agents of educational transformation in the Society 5.0 era, and their readiness in handling technological, pedagogical, and moral demands is vital to the future of education.